Lungun Music: The Batak Toba Andung Vocal Interpretation In Chamber Music - Simanjuntak, Yessica Yosia Virginia; sudirana, I Wayan (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
Lungun is a musical piece inspired by the andung Batak tradition of grief singing, expressing sorrow for a loved one. Andung songs are chanted by a pangandung (poet) using hata andung verses (Toba Batak fine literature) whose content tells the life history of someone who has died. Nowadays, the andung tradition has shifted, and many people cannot practice it; This is because many younger generations can no longer speak with hata andung, andung singing tends to be replaced with spiritual songs. Andung is unique in terms of lyrical and musical, andung is even a cultural heritage that the Batak community itself should preserve. The above problem requires the creator to work on Lungun music, which aims to discover the musical form and symbolic meaning. The method used is panca sthiti ngawi sani, which consist of five stages: (1) inspiration (ngawirasa), (2) exploration (ngawacak), (3) conception (ngarencana), (4) execution (ngawangun) and (4) production (ngabah). Lungun's musical work incorporates elements such as the Toba Batak scales, processed andung vocals, hata andung poems, rhythm processing, and Gondang Sabangunanplaying techniques into chamber music performances. Lungun music has three parts: part I is mula-mula (beginning), part II is andung (vocal lamentation singing), and part III is poda (message). The symbolic meaning expressed in Lungun music refers to the values found in the Toba Batak community: the Dalihan Na Tolu Batak philosophy, the five levels of Toba Batak death, and the seven Toba Batak philosophies.